Balance of Payments and Exchange Rates in ASEAN Countries: Granger Causality Test - Aprilia, Rini; Malia, Rizka (Universitas Ahmad Dahlan, 2022)
Fluctuations in the balance of payments are a reflection of the instability of the exchange rate; crisis factors also greatly affect the deficit or surplus in the balance of payments. If the exchange rate depreciates, a country will increase exports because domestic prices are relatively cheaper than foreign prices so that it is one of the competitive forces to increase exports, and vice versa if a country experiences appreciation, the country will increase imports. This study aims to analyze and compare whether there is a causal relationship between the balance of payments and currency exchange rates in ASEAN countries. This study uses the Granger Causality Test method, therefore the data of this study is in the form of a time series, namely the years 2005-2019. Only Myanmar and the Philippines have the exchange rate and balance of payments variables which have a causal relationship. This is in line with the curve in the introduction where the exchange rates of the two countries are relatively higher than those of Indonesia and Vietnam, which reach tens to tens of thousands of rupiah. This means that no matter how low the exchange rate (depreciation) is, there is no or little possibility for the countries of Indonesia and Vietnam to export, which reduces the current account, which is part of the balance of payments)